PENGARUH LINGKUNGAN KERJA DAN DINAMIKA KELOMPOK TERHADAP STRES DOSEN - Levi Padalulu (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The objective of this research is to obtain information on the effect of working environment, group dynamics to stress. The population of this research is the 100 lecturer’s of Flores University. The total number of the research sample was 80 lecturer’s and they were taken randomly. The this research methodology that was survey which were chosen by simple purposive random sampling technique. The data were colected with questionnaire and analyzed with path analysis. Result on the analyisis it is conculaded that (1) there is the significantly direct effect of working environment towards stress, (2) there is the significantly direct effect group dynamics towards stress and (3) there is the significantly direct effect working environment towards group dynamics.